POLA SEBARAN LOKASI MINIMARKET DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI KOTA DENPASAR - I Putu Agus Saskara; I Gusti Putu Anindya Putra; Komang Wirawan (UNHI PRESS, 2020)
The purpose of this study was to determine the distribution patterns of minimarket locations and what factors influence the distribution patterns of minimarkets in South Denpasar District. The research method uses a quantitative approach. The unit of analysis consists of 209 minimarket data points. For analytical purposes, the techniques used are the nearest neighbor analysis and buffer analysis. In the analysis of minimarket distribution patterns, it shows clustering patterns. Based on a buffer analysis consisting of three factors: demographic factors, service coverage factors and road network factors. From the analysis it was found that (1) spatial demographic factors did not affect the existence of minimarket locations in South Denpasar Regency; (2) service coverage factors found to be overlapping; (3) Road network factor, the location of minimarkets is more dominant in the local road network, this is due to the fact that local roads have a high level of accessibility and are in residential areas. In particular, the existence of minimarkets that follow the pattern of the road network greatly influences the success of the minimarket business.